Perlindungan Anak Yang Dipanggil Menjadi Saksi Dalam Kasus Pidana Oleh Peran Dinas Pengendalian Penduduk, Keluarga Berencana, Pemberdayaan Perempuan Dan Perlindungan Anak (PP2KPPA) : (Studi Di Dinas PP2KPPA Kota Gorontalo) (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
This study discusses the role of the Office of Population Control, Family Planning, women's empowerment, and Child Protection (DP2KP2A) of Gorontalo City against children who are called as witnesses in criminal action cases. The child has a special position in the law and needs protection and guidance so that his rights are guaranteed. Although the law provides protection, there are obstacles to its implementation. This study aims to determine the role of DP2KP2A and inhibitory factors in protecting witness children in Gorontalo. The research method used is descriptive qualitative by collecting data from relevant agencies and field observations. The results showed that DP2KP2A has an important role in providing protection to children who become witnesses. For example, by socializing and advocating to the community and providing assistance to children who become witnesses from the beginning he was dealing with the law. In addition, the psychological treatment of children who become witnesses becomes the attention of the government by providing free servants from direct psychological doctors for free. however, there are several obstacles, 1) administrative constraints that can hinder the continuity of the service in providing pendampngan to children who become witnesses. 2) time constraints that affect the effectiveness of Service. The conclusion of this study is Dp2kp2a Gorontalo city has a significant role in protecting witness children, but constraints such as time synchronization and administration affect the effectiveness of services. Therefore, further efforts are needed to improve coordination between related institutions and simplify administration to ensure the rights of children are properly protected.